Interpreting sustainability in economic terms: Dynamic efficiency plus intergenerational equity - Robert N. Stavins; Alexander F. Wagner; Gernot Wagner (Fondazione Eni Enrico Mattei (FEEM), 2002)
Economists have expended considerable effort to develop economically meaningful definitions of the somewhat elusive concept of “sustainability.” We relate such a definition of sustainability to well known concepts from neoclassical economics, in particular, potential Pareto improvements (in the Kaldor-Hicks sense) and inter-personal compensation. In the inter-temporal realm, we find that dynamic efficiency is a necessary but not sufficient condition for a notion of sustainability that has normative standing as a goal for public policy. We define sustainability as dynamic efficiency plus intergenerational equity. Further, we argue that it is not unreasonable for economists to focus on the efficiency element, leaving equity considerations to the political process. The analogy to the relationship between potential Pareto improvements and(intragenerational) transfers can facilitate discussions about sustainability, both within the economics community and as part of an interdisciplinary discourse, and makes the basic concepts easier to operationalize.
Keywords: Q2; Q3; 330; sustainability; dynamic efficiency; intergenerational equity; Nachhaltige Entwicklung; Generationengerechtigkeit; Wirtschaftliche Effizienz; Theorie